Partial Androgen Insensitivity Syndrome: aaPartial androgen insensitivity syndrome: An infrequent cause of pubertal gynecomastian infrequent cause of pubertal gynecomastia (Indian Journal of Case Reports, 2022)
Gynecomastia refers to an enlargement of the breast tissue in males, caused by proliferation of glandular breast tissue.1 Pubertal gynecomastia is a common condition seen in around 60% of the adolescent boys and in most of the cases it resolves spontaneously over 1 - 2 years.1 Persistent pubertal gynecomastia is less frequent and can be associated with underlying pathological condition. We report a case of persistent pubertal gynecomastia with micropenis and bifid scrotum due to partial androgen insensitivity syndrome (PAIS).